1976
DOI: 10.1037/0021-9010.61.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style, subordinate personality, and task type as predictors of performance and satisfaction with supervision.

Abstract: Interactions between leadership style, subordinate personality, and task type, and the effects of different combinations of these variables on group performance and satisfaction with supervision were investigated. Three different types of leaders were selected and trained; (a) high in human relations and high in task orientation, (b) low in human relations and high in task orientation, and (c) high in human relations and low in task orientation. Each leader worked with eight high-and eight low-dogmatism subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1976
1976
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The findings strongly suggest that the relationship-oriented leaders were more effective in creating a favorable and conducive atmosphere leading to high productivity in the groups led by them than in the groups led by the task-oriented leaders. It has been also suggested by others that relationship-oriented patterns of leadership tend to enhance members satisfaction (Stogdill, 1974;Weed, Mitchell and Moffitt, 1976). In the present research most likely the increased satisfaction was possibly responsible for generation of more ideas in the relationship-oriented leaders' groups than in the taskoriented leaders' groups.…”
Section: Discussionsupporting
confidence: 68%
“…The findings strongly suggest that the relationship-oriented leaders were more effective in creating a favorable and conducive atmosphere leading to high productivity in the groups led by them than in the groups led by the task-oriented leaders. It has been also suggested by others that relationship-oriented patterns of leadership tend to enhance members satisfaction (Stogdill, 1974;Weed, Mitchell and Moffitt, 1976). In the present research most likely the increased satisfaction was possibly responsible for generation of more ideas in the relationship-oriented leaders' groups than in the taskoriented leaders' groups.…”
Section: Discussionsupporting
confidence: 68%
“…Further evidence of the interaction between task type and follower preference for a task vs. relationship-oriented leader is offered by Weed et al (1976). This study found that the only type of task that was a significant moderator between leadership role and task performance was the difficult–ambiguous task.…”
Section: Opposing Roles Of Leadershipmentioning
confidence: 71%
“…According to Smith, Kendall, and Hulin (19691, job satisfaction is a result of people experiencing a fulfillment of values and needs through on-the-job experiences. Indeed, several studies support an association between manager-subordinate relationships and job satisfaction (Coltrin & Glueck, 1977; Kenis, 1978; Weed, Mitchell, & Moffitt, 1976). Further, to a large extent, satisfaction levels seem to result from similarity in attitudes between dyad members (Davis, 1969;Phillips & Hays, 1978).…”
mentioning
confidence: 99%